Iron, aluminium and chromium co-removal from atmospheric nickel laterite leach solutions - Wang, K.; Li, J.; McDonald, R.; Browner, Richard (Elsevier, 2017)
© 2017 Elsevier Ltd. Atmospheric leaching (AL) of low-grade nickel laterite ores often produces leach liquor containing significant amounts of trivalent iron, aluminium and chromium ions. These impurities are normally removed by increasing the leach liquor pH to precipitate these metals before the recovery of nickel, cobalt and other metal values. This paper documents an investigation of the removal of iron, aluminium and chromium from both synthetic and real nickel laterite AL leach solutions using single- and multi-stage precipitation methods. Single-stage precipitation experiments performed using synthetic leach solutions containing Fe(III) + Ni(II) + Al(III), Fe(III) + Ni(II) + Cr(III), and Fe(III) + Ni(II) + Al(III) + Cr(III) showed that greater losses of nickel to solids occurred in the presence of aluminium and chromium. Increasing the pH value of the solution and the precipitation temperature favoured the removal of iron, aluminium and chromium, but at a cost of greater nickel losses. However, by carefully controlling pH and temperature using a multi-stage precipitation process, the iron, aluminium and chromium can be rejected effectively by precipitation with minimal nickel loss and desirable sludge properties. The optimum conditions for a multi-stage precipitation process were found to be pH 3.0 and 55 °C in the first stage and pH 3.0 and 85 °C in the second stage. Using this approach, as much as 95% iron and chromium together with more than 80% aluminium can be removed; the level of nickel loss to the solid can be reduced to below 1%. The sludge showed a fast settling rate of 5.05 m/h following the addition of a cationic flocculant. Similar satisfactory results were also obtained when performing this multi-stage precipitation procedure with real leach solutions.